Sensor-based intervention to enhance movement control of the spine in low back pain: Protocol for a quasi-randomized controlled trial - Bianca M. P. Mourits; Lammert A. Vos; Sjoerd M. Bruijn; Sjoerd M. Bruijn; Jaap H. van Dieën; Maarten R. Prins; Maarten R. Prins (Frontiers Media S.A., 2022)
IntroductionChronic low back pain is a common condition that imposes an enormous burden on individuals and society. Physical exercise with education is the most effective treatment, but generally results in small, albeit significant improvements. However, which type of exercise is most effective remains unknown. Core stability training is often used to improve muscle strength and spinal stability in these patients. The majority of the core stability exercises mentioned in intervention studies involve no spinal movements (static motor control exercises). It is questionable if these exercises would improve controlled movements of the spine. Sensor-based exergames controlled with spinal movements could help improve movement control of the spine. The primary aim of this study is to compare the effects of such sensor-based exergames to static motor control exercises on spinal movement control.Methods and analysisIn this quasi-randomized controlled trial, 60 patients with chronic low back pain who are already enrolled in a multidisciplinary rehabilitation programme will be recruited. Patients will be randomly allocated into one of two groups: the Sensor-Based Movement Control group (n = 30) or the Static Motor Control group (n = 30). Both groups will receive 8 weeks of two supervised therapy sessions and four home exercises per week in addition to the rehabilitation programme. At baseline (week 1) and after the intervention (week 10), movement control of the spine will be assessed using a tracking task and clinical movement control test battery. Questionnaires on pain, disability, fear avoidance and quality of life will be taken at baseline, after intervention and at 6- and 12 months follow-up. Repeated measures ANOVAs will be used to evaluate if a significant Group x Time interaction effect exists for the movement control evaluations.DiscussionSensor-based spinal controlled exergames are a novel way to train spinal movement control using meaningful and engaging feedback. The results of this study will inform clinicians and researchers on the efficacy of movement control training for patients with low back pain.Ethics and disseminationEthical approval for this study protocol was obtained from the METC Brabant (protocol number NL76811.028.21).Trial registrationOpen Science Framework Registries (https://osf.io/v3mw9/), registration number: 10.17605/OSF.IO/V3MW9, registered on 1 September 2021.